Seasonal and spatial distribution of the phytoplankton in the pelagial of Lake Ohrid - Mitic, Vase (Macedonian Journal of Ecology and Environment, 1993)
Phytoplankton seccession is an important indicator for the stability of the plankton community of aquatic ecosystems. These investigations, in Lake Ohrid, have been done for a long period of time. The seasonal and spatial distribution of the phytoplankton in the pelagial of Lake Ohrid is presented in this paper. These results confirm the plankton stability in the pelagial of Lake Ohrid.